Cilostazol improves hyperglycemia-induced impaired vasculo-angiogenesis through stimulating adiponectin/adiponectin receptor 1/Sirtuin 1 signaling pathway. (25th November 2020) - Chao, T.H; Tseng, S.Y; Li, Y.H
Abstract: Background: Cilostazol is an antiplatelet agent with vasodilating effect working through increasing intracellular concentration of cyclic adenosine monophosphate (AMP). We and others have previously found that cilostazol has a favorable effect on vasculo-angiogenesis. However, there is no study to evaluate the effect of cilostazol on adiponectin and its receptors. Purpose: This study investigated the effects of cilostazol on adiponectin/adiponectin receptors and Sirtuin 1 (Sirt1)/AMP-activated protein kinase (AMPK) signaling pathway for preventing high glucose (HG)-induced impaired vasculo-angiogenesis in vitro and in vivo. Methods and results: Human umbilical vein endothelial cells (HUVECs), seeded onto Transwell insert, and human aortic smooth muscle cells (HASMCs), seeded onto 6-well plate at lower level, were co-cultured in HG condition (25 mM). Adiponectin concentrations in the supernatant of 6-welll-plate and Transwell insert were significantly higher when HASMCs were treated with cilostazol in a dose-response manner but not significantly changed when only HUVECs were treated with cilostazol. HG downregulated protein expression of adiponectin receptor-1 (adipoR1), adipoR2, and Sirt1 and phosphorylation of AMPKα1, whereas cilostazol treatment restored expression of adipoR1 and Sirt1 proteins and upregulated phosphorylation of AMPKα1 in HUVECs treated with HG but not adipoR2. The stimulating effect of cilostazol on AMPKα1 or Sirt1 was attenuated with Sirt1 or AMPKα1 gene knockdown, respectively. By using gene knockdown of adiponectin receptors or AMPKα1, or treatment of the Sirt1 inhibitor, our data showed that cilostazol prevented apoptosis, and stimulated proliferation, chemotactic motility and capillary-like tube formation in HG-treated HUVECs through adipoR1, AMPK, and Sirt1 signaling pathway but not adipoR2. Fifteen-week-old male ICR hyperglycemic mice, induced by streptozosin injection and high cholesterol diet feeding, were treated intraperitoneally with cilostazol (10 mg/kg) 2 times per day since day 1 to day 7 after hindlimb ischemia. Recovery of blood flow ratio (ipsilateral/contralateral) in the ischemic hindlimb 14–21 days after surgery and circulating CD34+CD45dim cells were significantly attenuated by adipoR1 knockdown but not adipoR2. Capillary density in the ischemic muscles was significantly lower in both adipoR1- and adipoR2-knockdown mice. Expression of Sirt1 as well as phosphorylation of AMPKα1/acetyl-CoA carboxylase and Akt/endothelial nitric oxide synthase in ischemic muscles were significantly attenuated by gene knockdown of adipoR1 or adipoR2. Conclusions: Our data suggest that cilostazol prevents high glucose-induced endothelial dysfunction in vascular endothelial cells as well as enhances vasculo-angiogenesis in hyperglycemic mice by upregulation of adiponectin/adipoR2 and its downstream signaling molecules, Sirt1/AMPK. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): The Ministry of Health and Welfare, Executive Yuan, Taiwan; The Ministry of Science and Technology, Executive Yuan, Taiwan